Improving antimicrobial prescribing in adults hospitalised with community-acquired pneumonia in a district general hospital of West Yorkshire - Muhammad Sami Khan; Umair Tariq; Ifrah Amjad; Abeera Zafar (Clinical Medicine)
Introduction: Community-acquired pneumonia (CAP) is a leading cause of morbidity and mortality in UK Healthcare, which is undoubtedly related to poor guideline adherence in CAP management.1 British Thoracic Society (BTS) has provided a standard of care for better clinical outcomes in CAP.2 We aimed to improve the antimicrobial prescribing in adult patients hospitalised with CAP in our hospital using quality improvement (QI) methodology. Materials and Methods: A QI project was conducted at Calderdale Royal Hospital, West Yorkshire. QI methodology was employed to improve the quality of antimicrobial prescribing. Baseline data were collected retrospectively from October to December 2023, and compared with post-intervention prospective data collected from February to April 2024. Local antimicrobial guidelines for CAP, consistent with BTS CAP guidelines 2009,2 were utilised as standard of care. QI interventions included: interactive presentation in medical grand rounds; distributing lanyard cards among doctors featuring local CAP guidelines; and posters exhibition in handover meetings as active reminders through senior on-call involvement. Outcome measures included: CURB 65 score documentation; antibiotic(s) prescription concordant with CURB 65 score and local guidelines; and antibiotic(s) review within 24 h of admission. Results and Discussion: We elected 88 adult patients (45 retrospective, 43 prospective), aged 18 and over, hospitalised with CAP. The post-intervention phase demonstrated substantial improvement in outcome measures compared with baseline: CURB 65 score documentation (from 44% to 98%); antibiotic(s) prescription concordant with CURB 65 score and local guidelines (from 49% to 89%); and antibiotic(s) review within 24 h (from 10% to 80%). Most common prescribing errors included missed atypical coverage in high-risk CAP and inappropriate use of intravenous antibiotics in low-risk CA, which improved in post-intervention phase. Conclusion: QI methodology can significantly enhance guideline adherence and appropriate antibiotic prescription in CAP management, which translates into better quality and safety in patient care. We recommend the nationwide encouragement of such QI projects to promote guideline-directed patient care and safe antibiotic stewardship leading to improved patient-reported outcomes.